Effect of treating tall fescue pasture with Mefluidide on performance of grazing steers - Moyer, Joseph L.; Lomas, Lyle W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Mefluidide (Embark® ) delays maturity and suppresses seed head formation in grasses. Mefluidide treatment increased the crude protein content of fescue pasture and improved daily gain of grazing steers by 14.3% (.21 lb per head daily).
Keywords: Beef; Fescue; Mefluidide; Performance; Steers